Efektivitas Edukasi Audiovisual Interaktif terhadap Peningkatan Pengetahuan dan Sikap Remaja dalam Pencegahan Stunting - Syafiq Maulana; Mohammad Dimas Dwihartono Syariat; Fatahillah Tsabit Fatoni; Febita Urva; Syaroifu Faizah Miftahul Janah; Aysha Nayla; Ufada Alidya Nadlifah; Nurlaili Susanti (Universitas Muhammadiyah Semarang, 2026)
Stunting continues to pose a substantial public health issue due to its long-term effects on physical growth and cognitive development. Adolescents are increasingly recognized as an important target group, given their future role as parents and the need to strengthen early health literacy to interrupt the intergenerational transmission of stunting. This study assessed the effectiveness of interactive audiovisual-based education in improving adolescents’ knowledge and attitudes toward stunting prevention. A pre-experimental study employing a one-group pre-test and post-test approach was conducted among 100 students at SMP Negeri 7 Malang, selected through simple random sampling. Data were obtained using validated questionnaires and analyzed using the Wilcoxon signed-rank test. Following the intervention, mean knowledge scores increased from 74.4 ± 1.10 to 80.8 ± 1.08, while mean attitude scores improved from 19.1 ± 0.29 to 20.7 ± 0.26 (p = 0.001). The proportion of respondents with good knowledge rose from 17% to 36%, and those demonstrating positive attitudes increased from 53% to 70%. These findings suggest that interactive audiovisual education is associated with short-term improvements in adolescents’ knowledge and attitudes toward stunting prevention.Keyword: stunting, health education, audiovisual, adolescent